2003
DOI: 10.1097/00004694-200311000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Premature Physeal Closure Following Distal Tibia Physeal Fractures

Abstract: The incidence and predictors of premature physeal closure (PPC) after pediatric distal tibial fractures were investigated. PPC was defined as evidence of growth plate disturbance on the injured side compared with the uninjured side. Ninety-two fractures were reviewed with at least 1 year of follow-up, or until physiologic closure of the growth plates. Twenty-five fractures (27.2%) were complicated by PPC, as confirmed by CT scan in most cases. Salter-Harris III and IV (medial malleolar type) fractures resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 18 publications
7
79
0
3
Order By: Relevance
“…Recent studies have suggested that Salter-Harris 1 and 2 fractures may have a higher rate of growth arrest than previously thought, perhaps up to 40 % [2,27]. In one study of Salter Harris 1 and 2 fractures, rates of premature physeal closure of 60 % were seen if the residual fracture gap was greater than 3 mm radiographically, and this gap often represented trapped periosteum [2]. Depending on the size and location of the growth arrest, and on the age of the child, premature closure may result in varus or valgus deformity, with or without shortening of the injured side (Figs.…”
Section: Complicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies have suggested that Salter-Harris 1 and 2 fractures may have a higher rate of growth arrest than previously thought, perhaps up to 40 % [2,27]. In one study of Salter Harris 1 and 2 fractures, rates of premature physeal closure of 60 % were seen if the residual fracture gap was greater than 3 mm radiographically, and this gap often represented trapped periosteum [2]. Depending on the size and location of the growth arrest, and on the age of the child, premature closure may result in varus or valgus deformity, with or without shortening of the injured side (Figs.…”
Section: Complicationsmentioning
confidence: 89%
“…Damage may occur at the time of initial injury, although anatomical reduction is also vital to prevent arrest secondary to displacement. Recent studies have suggested that Salter-Harris 1 and 2 fractures may have a higher rate of growth arrest than previously thought, perhaps up to 40 % [2,27]. In one study of Salter Harris 1 and 2 fractures, rates of premature physeal closure of 60 % were seen if the residual fracture gap was greater than 3 mm radiographically, and this gap often represented trapped periosteum [2].…”
Section: Complicationsmentioning
confidence: 99%
“…Repeated or delayed manipulation of physeal fractures should be avoided, so as to avoid additional damage to the physis with incurrent risks of premature closure. 38, 41 …”
Section: Treatment Strategiesmentioning
confidence: 99%
“…12, 38, 41, 49, 50 Fracture type, high energy trauma, higher initial displacement and multiple manipulation attempts are associated with growth arrest. 38 Barmada et al found higher rates of physeal arrest (60% vs. 17%) if a residual gap > 3 mm was seen at the physis for SH-I and II fracture patterns, 41 and recommended open reduction to remove entrapped periosteum in these settings.…”
Section: Complicationsmentioning
confidence: 99%
“…Other types of fractures, types III, IV, and V, however, may/will all result in bony formation at the injured site [13]. It has been estimated that in up to 30% of all children with growth plate-related injuries, undesirable bony repair, and bone bridge at the injury site hinder normal growth of the developing long bone in the affected limb [14, 15], which results in significant orthopaedic problems such as limb length discrepancy and bone angulation deformity [15, 16]. …”
Section: Growth Plate Injury and Current Treatmentsmentioning
confidence: 99%